2017
DOI: 10.11648/j.ijefm.20170503.13
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Management and Performance of Deposit Money Banks in Nigeria (1986 – 2011): An Investigation

Abstract: Liquidity and bank performance are key factors in determining the survival, growth, sustainability and performance of a banking system. Mistakes in liquidity planning and implementation can affect banking operations and might exhibit long term effect on the economy. The main aim of this study is to find empirical evidence of the impact of liquidity management on the performance of deposit money banks. 24 banks were surveyed which constitute the entire deposit money banking industry in Nigeria between 1986 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
3
26
2
1
Order By: Relevance
“…That's why the managers of sugar firms would increase the firm's profitability & value of its shareholder if they invest liquid assets efficiently & effectively. Edem, (2017) exerted that there lies significant and positive connection amongst liquidity management variables i.e. (liquidity & cash reserve ratios) and the performance variable ROE of Nigerian banks.…”
Section: 2mentioning
confidence: 97%
“…That's why the managers of sugar firms would increase the firm's profitability & value of its shareholder if they invest liquid assets efficiently & effectively. Edem, (2017) exerted that there lies significant and positive connection amongst liquidity management variables i.e. (liquidity & cash reserve ratios) and the performance variable ROE of Nigerian banks.…”
Section: 2mentioning
confidence: 97%
“…A few previous literature on liquidity showed that as an independent variable, it had a significant and positive effect on the firm performance's measures ROA, ROE & EPS (Banafa, 2016;Edem, 2017;Kahyani et al, 2016;Odalo & Achoki, 2016). Some studies depicted negative relationship of liquidity and firm's performance (Ahmad et al, 2015;Njimanted et al, 2017;Vintila & Nenu, 2016).…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…On the other hand, some literature regarding liquidity and firm's performance showed their positive impact on each other (Edem, 2017;Odalo & Achoki, 2016;Sheikhdon & Kavale, 2016;Tuffour & Boateng, 2017). Whereas, some authors observed negative relation among liquidity &firm's performance (Ahmad et al, 2015;Njimanted et al, 2017;Vintila & Nenu, 2016).…”
Section: 2mentioning
confidence: 99%
“…For instance, it was observed that some views concluded that liquidity management and performance are positively related, while others found that liquidity management and performance are negatively related. Some other studies, however, concluded that liquidity management and performance are not related (Ibe, 2013;Ndoka, Islami, & Shima, 2017;Daniel, 2017;Bassey & Moses, 2015). Nigeria adopted International Finacial Reporting Standard (IFRS) in 2012.…”
Section: Development Of Hypothesesmentioning
confidence: 99%